THE RELEVANCE OF SHEIKH AL WASIL TOMB AS HISTORICAL EVIDENCE OF THE SPREAD OF ISLAM IN KEDIRI - Ervin Yunus Evendi (Fakultas Adab dan Humaniora UIN Sunan Gunung Djati Bandung, 2022)
Syekh Wasil Syamsuddin for the citizens of Kediri is the figure of the first propagator of Islam in the city of Kediri. The story of Sheikh Al Wasil's character comes mostly from speech stories that developed in the community and is supported by artifacts in the form of epitaphs that are in the tomb, these artifacts are believed to be a marker of the early spread of Islam in Kediri or the year this character died. The background of Sheikh al Wasil's arrival in Kediri apart from spreading Islam was allegedly due to the invitation of Prabu Sri Aji Jayabaya to discuss the book of Musarar (Serat Jangka Jayabaya). In addition, another opinion emerged, namely the similarity of architecture in the Setono Gedong tomb complex with the tomb complex of Sunan Drajad in Lamongan. opinion is supported by the opinion that Sunan Drajad married a daughter of the Duke of Kediri, namely Retno Ayu Condro Sekar who is the daughter of Suryo Adilogo, so it is suspected that Sheikh Al Wasil was Suryo Adilogo. Thus there needs to be extracthistorical data through the critical historical method with 4 stages, namely heuristics, verification, interpretation and historiography. And in the preparation of this article the researcher used descriptive qualitative methods with data obtained from interviews, observations and literature studies. This research also aims to explore to explain the character of Sheikh Al Wasil in Kediri. Keywords: Syekh Al Wasil Syamsuddin; Islamic religion propagator; The relevance of the tomb of Syekh Al WasilAbstrak :Syekh Wasil Syamsuddin bagi warga Kediri merupakan sosok tokoh penyebar agama Islam pertama di Kota Kediri. Kisah ketokohan Syekh Al Wasil banyak berasal dari cerita tutur yang berkembang di masyarakat serta didukung oleh artefak berupa epitaph yang berada dalam makam, artefak tersebut dipercaya sebagai sebagai penanda masa awal penyebaran islam di kediri atau tahun meninggalnya tokoh ini. Latar belakang kedatangan syekh al wasil di Kediri selain untuk menyebarkan agama islam diduga karena adanya undangan Prabu Sri Aji Jayabaya untuk membahas kitab musarar (serat jangka Jayabaya). Selain itu muncul opini lain yakni adanya kesamaan arsitektur dalam kompleks makam setono gedong dengan kompleks makam sunan Drajad di Lamongan. opini tersebut didukung oleh pendapat bahwa Sunan Drajad menikahi seorang putri adipati Kediri yakni Retno Ayu Condro Sekar yang merupakan putri dari Suryo Adilogo, sehingga diduga syekh al wasil adalah suryo adilogo. Dengan demikian perlu ada upaya penggalian data sejarah melalui metode sejarah kritis dengan 4 tahap yakni heuristik,verifikasi,interpretasi dan historiografi. Dan dalam penyusunan artikel ini peneliti menggunakan metode kualitatif deskriptif dengan data yang diperoleh dari wawancara,observasi dan studi pustaka. Penelitian ini pun bertujuan untuk menggali fakta sejarah melalui makam syekh al wasil untuk menjelaskan ketokohan Syekh Al Wasil di Kediri.Kata kunci: Syekh Al Wasil Syamsuddin; Tokoh penyebar agama islam; Relevansi makam Syekh Al Wasil